2018
DOI: 10.1007/s00127-018-1554-6
|View full text |Cite
|
Sign up to set email alerts
|

Which mental disorders are associated with the greatest impairment in functioning?

Abstract: Our results highlight the value of complementary measures of functional impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
16
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 31 publications
7
16
0
9
Order By: Relevance
“…Impairments were most consistently associated with major depression, panic disorder, and ADHD after adjusting for class membership. This association is consistent with evidence for the special importance of these disorders in previous surveys among students (Verger et al, ) as well as in the general population (Comer et al, ; Edlund et al, ). However, the LCA showed that substantial proportions of the students with these disorders also had other diagnoses, making it important to consider the use of trans‐diagnostic approaches in treating these students (Barlow et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Impairments were most consistently associated with major depression, panic disorder, and ADHD after adjusting for class membership. This association is consistent with evidence for the special importance of these disorders in previous surveys among students (Verger et al, ) as well as in the general population (Comer et al, ; Edlund et al, ). However, the LCA showed that substantial proportions of the students with these disorders also had other diagnoses, making it important to consider the use of trans‐diagnostic approaches in treating these students (Barlow et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Together these findings, evidentially, suggest a significant and chronic burden in refugees due to poor mental health, impeding their functioning and possibilities to adapt. 1,98 When method of assessment is considered, the results reported here are largely in line with the results reported in earlier meta-analyses. [14][15][16] This could suggest that prevalence rates of anxiety, depression and PTSD in refugee populations do not change over time.…”
Section: Discussionsupporting
confidence: 90%
“…Together these findings, evidentially, suggest a significant and chronic burden in refugees due to poor mental health, impeding their functioning and possibilities to adapt. 1,98…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that DSM-5 has been introduced in 2013, the WHODAS 2.0 has not so far been widely adopted in mental health research and practice. Although Edlund et al [ 28 ] indicated that eating disorders ‘might be highly disabling’, in their nationally representative population surveys using the WHODAS 2.0, the authors did not include eating disorders because of their relatively low prevalence. The two studies that did assess a patient-reported version of the WHODAS in patients with an eating disorder either did not have a noneating disorder control group [ 29 ] or did not report separately on patients with an eating disorder [ 30 ].…”
Section: Global Burden Of Disease Studymentioning
confidence: 99%